Kinematic differences between upkick and downkick in undulatory underwater swimming - Higgs, A. J.; Pease, D. L.; Sanders, R. H. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Undulatory underwater swimming (UUS) is performed for up to 15 m of each lap in a swimming race, and is important for overall performance. This undulatory motion has two phases- the upkick (knee flexion and hip extension) and the downkick (the converse). This study assessed kinematic differences between the two phases, and determined whether these differences were related to performance in an elite sample. Each of the ten participants performed three 20 m UUS trials, and seven landmarks were manually digitised from the single camera view perpendicular to swimming direction. Differences between phases were found for vertical toe velocity, body wave velocity, hip and knee angular velocities and phase duration (p < 0.05), with differences in mean hip angular velocity and phase duration (p < 0.05) being strongly related to UUS performance.